Exploring Survival Strategies and Family Role in Micro-Family Food Business: Piloting for Interviews in Qualitative Research - Azman, Ana Batrisyia (2022)
A range of philosophical perspectives, techniques, and comprehensions are gleaned from the viewpoints of the participants in qualitative research. Understanding how people view their experiences and actions is a significant purpose. However, it could be challenging for a novice researcher to carry out the interview with a qualitative approach. Particularly in qualitative research, where it highlights the changes to the major study, the pilot study was a crucial component in assessing the viability and evaluation of the study. The significance of pilot studies, the techniques used, and the lessons acquired during the process are all described in this article. The pilot interview was conducted with two owners of the micro-family food businesses (MFFB), as preparation for a thesis in developing the research instruments further an in-depth understanding of the challenges, adaptation and the family role influences in family food business amid COVID-19 post-pandemic in Klang Valley, Selangor, Malaysia. In addition to demonstrating the benefits of pilot studies, this paper also discusses the changes that were made to the main research as a result of the pilot test. These account for the interview guide's adjustment, specifically the interview questions.